PENDEKATAN TECNOLOGICAL, ORGANIZATIONAL AND ENVIRONMENT CONTEXT DALAM MENGKAJI PERFORMA BISNIS PADA USAHA INDUSTRI EKONOMI KREATIF TERKAIT ADOPSI AI DI BIDANG PEMASARAN - Herwan Abdul Muhyi; Arianis Chan; Tetty Herawaty; Rani Sukmadewi; Gessan Kurnia Dewi (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the factors influencing the readiness for artificial intelligence (AI) adoption in marketing among business actors in the creative industry sector in West Java. The research employs a quantitative approach, collecting data through surveys and questionnaires from 226 respondents. Multiple regression analysis was conducted to examine the relationship between technological, organizational, and environmental factors on business performance. The results indicate that organizational context factors significantly influence AI adoption in marketing, while technological and environmental contexts do not show a significant impact. These findings provide insights for business practitioners in formulating more effective strategies for AI adoption to enhance business performance in the creative industry sector.